PENGARUH LATIHAN BARIER HOPS TERHADAP POWER OTOT TUNGKAI PADA TIM SEPAK TAKRAW GEMILANG JAYA PEKANBARU - Darmawan Abdullah; Zainur Zainur; Alimandan Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that athletes are less than optimal at jumping blocks and strokes (spikes), even though the football pulling game really needs leg muscle strength to jump, when blocks and hitting the ball are rarely unstoppable and does not hit the legs, so the opponent can easily hit looking for points. This type of research is a kind of experimental study to see the effect of the form of exercise, the aim of this research is to look at the effect of barrier hop training on leg muscle strength in the Takraw Gemilang Jaya Pekanbaru Team. The population in this research was the Takraw Gemilang Jaya team, good for 8 people. The sampling technique is the use of total sampling, where the total population is sampled. Data collection techniques were obtained from the pre-test and the post-test. The instrument in this study used vertical jump as an aid to measure leg muscle strength. The data is then statistically processed to test normality using the lilifours test at a significance level of 0.05α. Based on the analysis of the normality of the data X, it gives a LoMax of 0.183 and an Ltable of 0.285, which means LoMax <Ltable. while the variable Y produces LoMax of 0.152 and Ltable of 0.285. This means LoMax <L table. The analysis was performed with a t-test. Based on data analysis and discussion, it can be concluded that there is an effect of hop bary exercise against limb muscle strength in the Takraw Gemilang Jaya Pekanbaru football team, as shown by a Tcount of 6,790 and a table of 1,895. Means Thitung> Ttable At the level ɑ = 0.05.Key Words: Barier Hop exercise, Leg muscle strength